КАRL REICHL – TRANSLATOR AND RESEARCHER OF UZBEK FOLKLORE (Scientific journal of the Fergana State University, 2023)
The article informs about Karl Reichl as one of the well-known Turkologists who used the works of Uzbek folklorists in English and German languages. His work as a translator and researcher of Uzbek folklore, his translations into German and English, the content of his research and its structure are described. The foundations and methods of a comparative approach to Uzbek folklore in the world folklore are identified in the example of Karl Reichl's English translation and research.